THE EFFECT OF SALES GROWTH, PROFITABILITY, AND LEVERAGE ON TAX AVOIDANCE (EMPIRICAL STUDY OF PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE IDX 2020-2023) - Syaifudin, Imam; Hadnan, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine the effect of sales growth, profitability, and leverage on tax avoidance in property and real estate companies listed on the Indonesia Stock Exchange during 2020–2023. The research applies a causal quantitative approach with purposive sampling, resulting in 26 companies as the sample. Data were analyzed using multiple linear regression. The findings reveal that sales growth and leverage have no significant effect on tax avoidance, while profitability has a significant positive effect. These results provide insights for company management and tax regulators in formulating strategies to minimize tax avoidance practices.